Oral History Program Interview: Hazel Fay Mitchell - Mitchell, Hazel Fay
Born in Mountain Home, Baxter County, Arkansas, in 1918, Mitchell came to Arvin, California in 1928. Her interview includes describing people from a government camp, how abusing welfare has not changed since the program's inception, why The Grapes of Wrath is inaccurate, what "Okie" meant to the migrants, the importance of church, when the effects of the Great Depression occur, getting a sack of cotton confiscated at the California border, schoolyard problems with non-migrant children, and some home remedies for injuries and sickness.